The Effect of Preoperative Health Education, Delivered as Animation Videos, on Postoperative Anxiety and Pain in Femoral Fractures - Wang, Yuewei; Huang, Xueqin; Liu, Zhili (Frontiers in Psychology, 2022)
Objective: This article explores the effect of preoperative health education, in the form of animation videos, on postoperative self-reported pain levels and anxiety in femoral fractures. Methods: Ninety cases of femoral fracture were divided at random into the oral instruction group, the recorded video group, and the animation video group, with 30 cases in each group. Sociodemographic data were collected the day before surgery. Health education was then offered in one of three ways: orally, using a recorded video, or using an animation video. On days 2, 4, and 7 after surgery, the state-trait anxiety inventory (STAI) and the visual analog scale (VAS) were used to assess postoperative anxiety and pain levels, respectively, in the participants. Results: At different time points during the evaluation, total anxiety scores in the animation and recorded video groups were significantly lower than in the oral instruction group (P < 0.01), and the pairwise comparisons indicated statistically significant differences (F = 11.04, 10.06, 10.37, P < 0.01). However, the levels of postoperative pain in the animation and recorded video groups were not significantly different (P > 0.05). STAI scores in the three groups were found to have significant interactions with the measurement time (F = 6.74, P < 0.01). However, there were no apparent interactions between the VAS score and the measurement time (F = 1.31, P > 0.05) in the three groups. Conclusion: Preoperative health education with the aid of multimedia is more effective than oral instruction in lowering patients’ postoperative anxiety and pain levels. In addition, animation videos are superior to recorded videos in mitigating postoperative anxiety. Whether the two approaches differ in reducing postoperative pain in bone fractures remains to be further tested.